TESTS OF POLY ACRYLIC ACID (PPA) INHIBITOR ON BARIUM SULFATE SCALE INHIBITION EFFEICIENCY - Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2008)
Injection water (containing sulphate ion) is injected into reservoir (containing barium ion), mixture of incompatible water types results in barium sulphate scale occurrence.